2009
DOI: 10.1039/b908652h
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional bisphosphonate complexes for the diagnosis and therapy of bone metastases

Abstract: Easily synthesised and structurally well-defined novel imaging/therapeutic radiopharmaceutical agents for bone metastases are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 19 publications
5
79
0
1
Order By: Relevance
“…Therefore, the concept of bone-targeted delivery system is the use of biomolecules conjugated with bisphosphonates as ligands targeting bone mineral (Cole, Vargo-Gogola, & Roeder, 2016). Clinical applications investigating bisphosphonates as a targeting ligand include metabolic bone diseases such as osteoporosis (Bhandari, Newa, Chapman, & Doschak, 2012; Fujisaki et al, 1997; Morioka et al, 2010), bone infection (Houghton et al, 2008), rheumatoid arthritis (Hirabayashi et al, 2001), osteosarcoma, and cancer metastases to bone (Klenner et al, 1990; Reinholz et al, 2010; Torres Martin de Rosales, Finucane, Mather, & Blower, 2009). Intravenous injection or oral administration of bisphosphonate-conjugated vehicle delivered the desired compounds to bone due to their high affinity for calcium crystals (Widler, Jahnke, & Green, 2012).…”
Section: Drug Delivery Strategies In Bone Disordersmentioning
confidence: 99%
“…Therefore, the concept of bone-targeted delivery system is the use of biomolecules conjugated with bisphosphonates as ligands targeting bone mineral (Cole, Vargo-Gogola, & Roeder, 2016). Clinical applications investigating bisphosphonates as a targeting ligand include metabolic bone diseases such as osteoporosis (Bhandari, Newa, Chapman, & Doschak, 2012; Fujisaki et al, 1997; Morioka et al, 2010), bone infection (Houghton et al, 2008), rheumatoid arthritis (Hirabayashi et al, 2001), osteosarcoma, and cancer metastases to bone (Klenner et al, 1990; Reinholz et al, 2010; Torres Martin de Rosales, Finucane, Mather, & Blower, 2009). Intravenous injection or oral administration of bisphosphonate-conjugated vehicle delivered the desired compounds to bone due to their high affinity for calcium crystals (Widler, Jahnke, & Green, 2012).…”
Section: Drug Delivery Strategies In Bone Disordersmentioning
confidence: 99%
“…Furthermore, this ligand needed to contain a functional group to allow its coupling to a PNA oligomer. Our attention rapidly turned to 2,2′-Dipicolylamine (Dpa) derivatives, which have already been intensively used in nuclear chemistry and which can be furthermore easily functionalized [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Thus, the ligand 2-azido-N,N-bis((pyridin-2-yl)methyl)ethanamine (Dpa-N 3 , Scheme 1) was prepared in a one-step synthesis starting from the known compound 2-(bis(pyridin-2-ylmethyl)amino)ethanol [51] (Dpa-OH) with triphenyl phosphine, diisopropyl azodicarboxylate and diphenylphosphoryl azide in THF (Scheme 1).…”
Section: Synthesis Of Dpa-n 3 [Re(co) 3 (Dpa-n 3 )]Br and A Dpa-conmentioning
confidence: 99%
“…8,20,21,33 Both Co 0.16 Fe 2.84 O 4 @NaYF 4 (Yb, Er)-BP-PEG and Fe 3 O 4 @NaYF 4 (Yb, Tm)-BP-PEG particles showed a high affinity to 99m Tc-DPA-ale (data not shown) and 64 Cu-(DTCBP) 2 , which has two uncoordinated bisphosphonate groups, 8,20 with up to 96% labeling efficiency (Table S5). The ability to bind readily with [ 18 F]-fluoride and bisphosphonate conjugates of 64 Cu and 99m Tc offers potential applications in PET and SPECT imaging.…”
Section: Resultsmentioning
confidence: 99%
“…9,11 The majority of current multimodality contrast agents are based on superparamagnetic iron oxide NPs, 1214 while a few examples of Gd 15,16 or Mn 17 containing NPs have also been reported. Since Weissleder et al 18 reported their pioneering work on multimodal imaging, combinations of NPs and functional polymers 19 or polydentate ligands 8,20,21 have been widely applied to obtain multifunctional agents. 14,15 An alternative approach is hybrid inorganic nanocomposites containing two materials with different properties, such as Fe 3 O 4 @NaGdF 4 NPs, 22 NaYF 4 @Fe x O y , 23 and Fe 3 O 4 @LnF 3 .…”
Section: Introductionmentioning
confidence: 99%